2019
DOI: 10.17113/ftb.57.01.19.5816
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Nonthermal Technologies

Abstract: Due to the high amount of biologically active compounds, basil is one of the most popular herbs. However, several outbreaks have been reported in the world due to the consumption of basil contaminated with different food pathogens. The aim of this study is to apply nonthermal and ecologically friendly approach based on photosensitization for microbial control of basil which was naturally contaminated with mesophils and inoculated with thermoresistant food pathogen Listeria monocytogenes 56Ly. The obtained data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Sodium Magnesium Chlorophyllin is a water-soluble derivative of natural chlorophyll, and holds approval as food additive E140. Due to its excellent biocompatibility, CHL has been successfully applied for the Photodynamic Decontamination of food [27,28], as well as the photodynamic killing of bacterial plant pathogens [5]. As expected, due to the lack of cationic moieties that interact with the cell wall/membrane of Gram-bacteria [6], CHL is not phototoxic against Gram-bacteria without cell-wall permeabilizing agents.…”
Section: Discussionmentioning
confidence: 82%
“…Sodium Magnesium Chlorophyllin is a water-soluble derivative of natural chlorophyll, and holds approval as food additive E140. Due to its excellent biocompatibility, CHL has been successfully applied for the Photodynamic Decontamination of food [27,28], as well as the photodynamic killing of bacterial plant pathogens [5]. As expected, due to the lack of cationic moieties that interact with the cell wall/membrane of Gram-bacteria [6], CHL is not phototoxic against Gram-bacteria without cell-wall permeabilizing agents.…”
Section: Discussionmentioning
confidence: 82%
“…Paskeviciute et al (2019) used chlorophyllin to reduce the microbial load in basil. They reported that soaking the basil in chlorophyllin and exposing it to light at 405 nm could be a method to increase the safety and shelf life basil [ 82 ].…”
Section: Application Of Recovered Chlorophylls In Functional Foodsmentioning
confidence: 99%
“…The use of natural PS grows as the demand for natural products increases, following the recent desires of consumers. Some examples of PSs obtained from nature are hypericin (Hyp), coumarins, furocoumarins, chlorophyllin (Chl), curcumin, and riboflavin (vitamin B2) (Bonifácio et al, 2018;Maisch et al, 2014;Otieno et al, 2020;Paskeviciute et al, 2019). The Hyp extract is a natural pigment obtained from the plant traditionally known as St John's wort (Hypericum perforatum) widely used as natural PS and considered one of the most powerful PS in nature (Lukšiene & Zukauskas, 2009).…”
Section: Photosensitizersmentioning
confidence: 99%
“…curcumin (Corrêa et al, 2020;Tao et al, 2019;Temba et al, 2019;Tosati et al, 2018) and chlorophyllin (Josewin et al, 2018;Paskeviciute et al, 2018;Paskeviciute et al, 2019;.…”
Section: Agrifood Applicationsmentioning
confidence: 99%
See 1 more Smart Citation